Effect of variety and weeding regime on the yield components and yield of Aus rice (Journal of the Bangladesh Agricultural University, 2014)
A field experiment was carried out at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, during the period from April to July 2012 to study the effect of variety and weeding regime on the yield components and yield of Aus rice. The experiment was laid out in a randomized complete block design with three replications. The experimental treatments comprised four varieties viz. BR 26, BRRI dhan27, BRRI dhan48 and Pariza; and five weeding treatments viz. no weeding, one hand weeding at 20 DAS(Days after sowing), two hand weeding at 20 DAS and 30 DAS, three hand weeding at 20, 30 and 40 DAS and weed free. Here broadcasting method of planting was used. Results revealed that varieties had significant effect on plant height, number of total tillers hill-1, number of effective tillers hill-1, number of non-effective tillers hill-1, number of grains panicle-1, number of unfilled spikelets panicle-1, 1000-grain weight, grain yield, straw yield, biological yield and harvest index. Grain yield was the highest in BRRI dhan48. Weeding regime had also significant effect on all the studied crop parameters except 1000-grain weight. The highest grain yield was obtained from weed free condition followed by three, two and one weeding conditions. Interaction between variety and weeding regime significantly influenced all the studied crop parameters except 1000-grain weight and harvest index. In interaction it was observed that the highest grain yield was obtained from BRRI dhan48 under two weeding condition. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18198 J. Bangladesh Agril. Univ. 11(1): 17-21, 2013